2015
DOI: 10.5937/ekopolj1502325i
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of MIRR method application for evaluation of investments in agriculture: An example of pigs fattening

Abstract: In the case of some agricultural investments, often net cash flow changes its sign from positive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…As a more practical version of IRR, the real-life applications include: the analysis of investment in pigs fattening-evaluate the growth rate and the further economics revenue; and the analysis of watershed projects. According to the research conducted by Ivanovic et al [29], they had a conclusion that this investment is economically benefit for the investor because the MIRR was higher than cost of capital. Moreover, the application of MIRR helps in the research of watershed evaluation.…”
Section: Modified Internal Rate Of Return Mirrmentioning
confidence: 99%
“…As a more practical version of IRR, the real-life applications include: the analysis of investment in pigs fattening-evaluate the growth rate and the further economics revenue; and the analysis of watershed projects. According to the research conducted by Ivanovic et al [29], they had a conclusion that this investment is economically benefit for the investor because the MIRR was higher than cost of capital. Moreover, the application of MIRR helps in the research of watershed evaluation.…”
Section: Modified Internal Rate Of Return Mirrmentioning
confidence: 99%
“…Moreover, the IRR may have a non-unique solution. These issues have attracted various researchers to develop alternative investment evaluation methods to overcome this problem such as the MIRR method, which has become most frequently used in capital budgeting practices (Solomon, 1956;Lin, 1976;Athanasopoulos, 1978;Balyeat et al, 2013;Ivanović et al, 2015;Sabri & Sarsour, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The MIRR assumes that the returns obtained from the positive cash flows of an investment project will be reinvested at the external rate of return, which is formally equal to the equity's cost of capital. Some financial analysts assert on implementing the MIRR method for both conventional and non-conventional investment projects (Bernhard, 1979;McDaniel et al, 1988;Kelleher & MacCormack, 2004;Kierulff, 2008;Balyeat et al, 2013;Ivanović et al, 2015;Kengatharan, 2016), although the MIRR formula is, in fact, simply an additional exhibition of the NPV (Kulakova & Kulakov, 2014). On the other hand, Kulakov and Kastro (2017) concluded that the IRR method was appropriate in evaluating investment with conventional rather than nonconventional projects.…”
Section: Introductionmentioning
confidence: 99%
“…Having in mind variability of market prices,Zekić et al (2007) stated that pig producers have an uncertain position, while the supply of processing industry is unstable Zekić et al (2008). determined economic and technological challenges related to the production of piglets and fattened pigs on family farms Ivanović et al (2015). indicated that economic evaluation of investments in pig production requires application of modified internal rate of return -MIRR (instead of traditional internal rate of return approach) due to a significant variation of net cash flow in pig fattening operation.…”
mentioning
confidence: 99%